Paradigma Progresif dan Maqashid Syariah: Manhaj Baru Menemukan Hukum Responsif - Maulidi, Maulidi (UIN Sunan Kalijaga, 2015)
Law both Islamic law and positive law has been more textual normative. This viewpoint is believed to occur because the law must have the principle of legality postscript found in the text (statutory law). To borrow a phrase in the study of Islamic Emirate of Muhammad, Islam is a divine source- oriented Insaniah (ilahiyul masdar insaniyul maudlu'). Sui generis- positivistic paradigm is considered by legal experts postmodernists are not sufficient to understand and find the law in the contemporary era. One of the legal experts Indonesia, Satjipto Raharjo also provide strong criticism against the way of thinking of positivistic-normative. According to this paradigm precisely the legal handcuff themselves to find substantive justice, especially in the absence of the text. Hence judges (mujtahid) required to be more creative and progressive thinking in the interpretation/ijtihad. The notion of progressive legal paradigm is actually trying to understand and find maqasid sharia-based law (legal purposes) to achieve the objectives of the law. Integration and interconnection of scientific disciplines become keywords in this paradigm, as a new form of legal epistimologi bid that is sui generis-cum empirisuntuk find solutions to the problems of contemporary law.